Healthcare utilisation and expenditure patterns for cardio-metabolic diseases in South Asian cities: the CARRS Study. Issue 9 (30th September 2020) - Gupta, Priti; Singh, Kalpana; Shivashankar, Roopa; Singh, Kavita; Vamadevan, Ajay; Mohan, V; Kadir, Muhammad Masood; Tandon, Nikhil; Narayan, K M; Prabhakaran, Dorairaj; Ali, Mohammed K
Abstract : Objective: To estimate average annual expenditures per person, total economic burden and distress health financing associated with the treatment of five cardio-metabolic diseases (CMDs—hypertension, diabetes, heart disease (angina, myocardial infarction and heart failure), stroke and chronic kidney disease) in three metropolitan cities in South Asia. Design: Cross-sectional surveys. Setting: We analysed community-based baseline data from the Centre for cArdio-metabolic Risk Reduction in South Asia (CARRS) Study collected in 2010–2011 representing Chennai and New Delhi (India), and Karachi (Pakistan). Participants: We used data from non-pregnant adults (≥20 years) from the aforementioned cities that responded to a cost-of-illness questionnaire. We estimated health utilisation and expenditures among those reporting taking treatment(s) for the aforementioned CMDs in the last 1 year. We converted all costs to International Dollars (Int 2011) and inflated to 2018 values. The annual costs per person were stratified by city, sociodemographic characteristics, contributor of costs and financing methods. The total economic burden of CMDs for each city was projected using age-standardised prevalence and per-person costs of diseases reported in CARRS, applying these to population data from the most recent census. We also calculated distress financing (DF) as having to borrow or sell assets to pay for CMD treatment and identified sociodemographic groups at most risk of DF using multiple regression. Results: Of 16 287 CARRS participants, 2883 (17.7%) reported receiving treatment for CMDs. The total annual expenditures reported per patient for CMDs ranged from Int358 to Int2425. Medications constituted 46% of total direct expenditures and out-of-pocket (OOP) expenditures accounted for nearly 80% of financing these health expenditures. Total economic burdens of CMDs were Int0.42 billion, Int3.4 billion and Int1.4 billion in Chennai, New Delhi and Karachi, respectively. Overall, 36.1% experienced DF, and women (OR=4.4), unemployed (OR=10.7) and uninsured (OR=8.1) adults experienced higher odds of DF. Conclusion: CMDs are associated with large economic burdens in South Asia. Due to most payments coming from OOP expenditures and limited insurance, the odds of DF are high.